Pharmacokinetics and Pharmacodynamics of Glyburide: Insights for Optimizing Treatment in Type 2 Diabetes - Alfaqeeh, Mohammed; Khairinisa, Miski Aghnia; Permana, Hikmat (Indonesian Journal of Clinical Pharmacy, 2024)
Glyburide is a widely used oral antidiabetic agent for managing type 2 diabetes. Despite its long history, evolving insights into its pharmacokinetics (PK) and pharmacodynamics (PD) have highlighted knowledge gaps, especially in the context of genetic variability, drug-drug interactions, and use in special populations. This narrative scoping review synthesizes recent evidence to provide a comprehensive and updated understanding of glyburide’s PK/PD profiles.  A thorough literature search of studies published in English, including manual reference checks, was conducted. Glyburide exhibits complex pharmacokinetics, extensive absorption throughout the gastrointestinal tract, significant plasma protein binding, hepatic metabolism via CYP2C9 and CYP3A4 enzymes, and predominantly renal elimination. Its pharmacodynamic effects involve stimulating insulin secretion and enhancing peripheral insulin sensitivity. Common side effects include hypoglycemia and weight gain, while drug-drug interactions and monitoring are crucial for safe and effective use. Understanding glyburide’s pharmacokinetics and pharmacodynamics is key to optimizing diabetes management. Tailoring dosages based on patient factors can improve efficacy, minimize adverse effects, and enable personalized care. Further research on genetic influences, drug interactions, and its use in special populations is needed to refine treatment strategies and enhance safety and effectiveness.